Adrenergic receptors and metabolism: role in development of cardiovascular disease - Ciccarelli, Michele; Santulli, Gaetano; Pascale, Valeria; Trimarco, Bruno; Iaccarino, Guido (Frontiers in Physiology, 2013)
Activation of the adrenergic system has a profound effects on metabolism. Increased circulating catecholamine and activation of the different adrenergic receptors deployed in the various organs produce important metabolic responses which include: 1) increased lipolysis and elevated levels of fatty acids in plasma, 2) increased gluconeogenesis by the liver to provide substrate for the brain and 3) moderate inhibition of insulin release by the pancreas to conserve glucose and to shift fuel metabolism of muscle in the direction of fatty acid oxidation. These physiological responses, typical of the stress conditions, are demonstrated to be detrimental for the functioning of different organs like the cardiac muscle when they become chronic. Indeed, a common feature of many pathological conditions involving over-activation of the adrenergic system is the development of metabolic alterations which can include insulin resistance, altered glucose and lipid metabolism and mitochondrial dysfunction. These patterns are involved with a variably extent among the different pathologies , however they are in general strictly correlated to the level of activation of the adrenergic system. Here we will review the effects of the different adrenergic receptors subtypes on the metabolic variation observed in important disease like Heart Failure.